PERLINDUNGAN PULAU-PULAU TERLUAR INDONESIA BERDASARKAN KONSEP NEGARA KEPULAUAN - Yeheschiel Bartin Marewa; Edgar Michael Parinussa (Paulus Law Journal, 2020)
The Unitary State of the Republic of Indonesia is an archipelagic country with the largest number of islands in the world and has abundant wealth, including those contained in the outer islands. However, it turns out that the Indonesian government has not fully empowered and managed the outer islands optimally. This study aims to analyze the protection of Indonesia's outer islands based on the concept of an archipelago state.The results show that the existence of the outer islands in Indonesia has received international recognition based on the United Nations Convention on The Law of the Sea 1982 through the use of archipelago baseline. Protection of the outer islands is carried out in the form of state policies through statutory regulations and any management actions.